1991
DOI: 10.1165/ajrcmb/5.5.437
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Inactivation of α1-Proteinase Inhibitor by Alveolar Macrophages from Healthy Smokers Requires the Presence of Myeloperoxidase

Abstract: The aim of this work was to study the ability of human alveolar macrophages (AM) of 10 healthy smokers to inactivate alpha 1-proteinase inhibitor (alpha 1PI). Purified alpha 1PI was incubated for 45 min, with human alveolar macrophages before and after stimulation by phorbol myristate acetate (PMA) or opsonized zymosan. As a positive control, the same experiments were performed in parallel with blood human neutrophils (PMN). Results are expressed as percentage of inactivation of alpha 1PI as evaluated from its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…These findings suggest that the synthesis of peroxynitrite is the major mechanism by which AMs may inactivate antiproteases. In contrast, WALLAERT et al [34] demonstrated that PMA-stimulated AMs do not inactivate α 1 -PI unless myeloperoxidase, released from PMNs, is present. In the cell-free PMN supernatant, we found myeloperoxidase activity and reactive oxygen metabolites, as indicated by the generation of methionine sulphoxide.…”
Section: Discussionmentioning
confidence: 89%
“…These findings suggest that the synthesis of peroxynitrite is the major mechanism by which AMs may inactivate antiproteases. In contrast, WALLAERT et al [34] demonstrated that PMA-stimulated AMs do not inactivate α 1 -PI unless myeloperoxidase, released from PMNs, is present. In the cell-free PMN supernatant, we found myeloperoxidase activity and reactive oxygen metabolites, as indicated by the generation of methionine sulphoxide.…”
Section: Discussionmentioning
confidence: 89%
“…A more promising avenue of investigation may be the measurement of circulating or excreted elastin degradation products [15]. Neutrophils may suppress the antiprotease capacity of the ELF through two pathways: the secretion of large quantities of serine proteases that bind antiprotease molecules, and the generation of oxygen-derived free radicals that may inactivate antiproteases either directly [3] or in combination with myeloperoxidase [20]. In the present study, the BAL antielastase activity was lower in samples with higher neutrophil counts, but this tendency did not translate into a statistically significant correlation overall.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 AT contains methionine at the "P1 position," which is located in the reactive site, and determines the specificity of inhibition. Various oxidant radicals such as peroxide, the hydroxyl radical, hypochloride, chloramine, and peroxynitrite 22,23 change the methionine into methionine sulfoxide, and such modified forms of AT lose the inhibitory activity against proteinases. Furthermore, such an oxidized form of AT has the function of monocyte activation.…”
mentioning
confidence: 99%